2006
DOI: 10.2466/pr0.98.1.111-120
|View full text |Cite
|
Sign up to set email alerts
|

Selected Organizational Outcome Correlates of Spirituality in the Workplace

Abstract: This study addressed the feasibility, practicality, and effects of a management style defined as "Management-by-Virtues," a management philosophy and practice based on virtues derived from religious beliefs. The study focused on Management-by-Virtues as practiced in Christian firms and assessed the effect that Management-by-Virtues could have on such organizational outcomes as employees' Organizational Commitment, Job Satisfaction, and propensity to go beyond the call of duty in carrying out organizational tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Indeed, workplace spirituality may emerge through shared norms -and potentially values -that support spirituality. For example, there has been empirical evidence that perceptions that the organization has a spiritual orientation correlates with organizational identification and commitment (Milliman et al 2003;Nur and Organ 2006;Kolodinsky et al 2008;. Similarly, Jurkiewicz and Giacalone (2004) argued that workplace spirituality is "a measurable aspect of an organization's culture" (p. 130) which is expressed through 10 core values: benevolence, generativity, humanism, integrity, justice, mutuality, receptivity, respect, responsibility, and trust.…”
Section: An Integrative Model Of Workplace Spirituality and Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, workplace spirituality may emerge through shared norms -and potentially values -that support spirituality. For example, there has been empirical evidence that perceptions that the organization has a spiritual orientation correlates with organizational identification and commitment (Milliman et al 2003;Nur and Organ 2006;Kolodinsky et al 2008;. Similarly, Jurkiewicz and Giacalone (2004) argued that workplace spirituality is "a measurable aspect of an organization's culture" (p. 130) which is expressed through 10 core values: benevolence, generativity, humanism, integrity, justice, mutuality, receptivity, respect, responsibility, and trust.…”
Section: An Integrative Model Of Workplace Spirituality and Commitmentmentioning
confidence: 99%
“…Indeed, evidence has been reported that some dimensions of workplace spirituality are strongly and positively related to such attitudes as organizational commitment, intrinsic work satisfaction, and job involvement (Milliman et al 2003;Nur and Organ 2006;Rego and Cunha 212 C. Vandenberghe 2008). However, despite this preliminary evidence, our understanding of the role that workplace spirituality plays in work attitudes remains limited.…”
mentioning
confidence: 99%
“…The research literature to date provides some evidence of this link. For example, spiritual individuals in the workplace are more likely to demonstrate greater fairness and kindness (Baiberman & Whitty, 1997), enhanced teamwork (Mitroff & Denton, 1999;Neck & Milliman, 1994), increased trust and honesty within their organisations (Brown, 2003;Krishnakumar & Neck, 2002), increased awareness of needs of colleagues (Cash & Gray, 2000), higher incidences of organizational citizenship behaviour OCB (Nur & Organ, 2006), and expression of more subordinate supervisor behaviour (Beazley & Gemmill, 2006). The spiritual ones are prone to perceive the ethical nature of business issues more clearly ( Giacalone & Jurkiewicz, 2003b) and are more sensitive to corporate social performance (Giacalone, Paul & Jurkiewicz, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, why do spiritual individuals have greater organisational commitment (Milliman, Czaplewski & Ferguson, 2003), increased job motivation (Jurkiewicz & Giacalone, 2004), increased productivity (Duchon & Plowman, 2005), and greater job satisfaction (Nur & Organ, 2006)? Perhaps, at least partially, it is because they see work as a calling, not just a job; and it is a job in which they want to do the best they can, with humility and while respecting others, for example.…”
Section: Phronesis and Spiritual Agents At Workmentioning
confidence: 99%
“…Indeed, research to date does provide some evidence of this relationship (Beazley & Gemmill, 2006;Biberman & Whitty, 1997;Cash & Gray, 2000;Giacalone & Jurkiewicz, 2003a;Giacalone, Paul, & Jurkiewicz, 2005;Krishnakumar & Neck, 2002;Mitroff & Denton, 1999;Neck & Milliman, 1994;Nur & Organ, 2006). What is unclear, however, in the spirituality in the workplace (from now on, SWP) literature is why and how an individual's spirituality influences their ethical performance within an organisational context.…”
Section: Introductionmentioning
confidence: 99%